A Review of the Effectiveness of Foreign Language Enjoyment and Foreign Language Classroom Anxiety on Learners' Engagement and Attainment - Shen, Jingping (Frontiers in Psychology, 2021)
Cognitive factors are not the fundamental determinants of success in language learning. Foreign language attainment depends on both cognitive and affective factors, highlighting the deeper impacts of the former. Some scholars started to investigate affective issues, particularly negative emotions in language learning studies; nevertheless, reducing negative emotions such as anxiety should be accompanied by the development of positive emotions (e.g., well-being, autonomy, & enjoyment). Since then, a great number of researchers have examined the impact of anxiety and enjoyment in foreign language literature, particularly after the introduction of reliable and valid foreign language classroom anxiety (FLCA) and foreign language enjoyment (FLE) scales. So, the present study aims to review contemporary scholarly articles and books in this regard. Findings suggest that there has been a major interest in the evaluation of FLCA and FLE across a variety of dimensions including personality traits, interpersonal characteristics, and classroom conditions. The central issues are summarized into three categories of the relationship between FLCA and FLE, the robustness of respective scales, and the impact of individual and interpersonal factors. Hence, this research attempts to highlight probable gaps and areas for further examinations to help enrich the literature and improve the theoretical knowledge.